Optimizing the manganese and silicon content for hot dip galvanizing of 3rd generation advanced high strength steels⋆. Issue 1 (14th February 2014) - Staudte, J.; Mataigne, J. M.; Del Frate, F.; Loison, D.; Cremel, S.
Abstract : The influence of variable Manganese content (2.4−4.6 wt%), while keeping constant Silicon (1.5 wt%) and Chromium (0.3 wt%) levels, and variable oxidation potential of the annealing atmosphere on hot dip galvanizability was investigated. Surface oxides prior to hot dip galvanizing were analyzed and coating quality assessed. The increasing oxidation potential of the annealing atmosphere led to a transition from external to internal selective oxidation of Mn, Si and Cr; their enrichment at the surface could be reduced and the metallic iron at the surface was increased. Hot dip galvanizability could thus be obtained up to 2.9%Mn. With increasing Mn content, the surface was covered by a rising amount of Mn-oxides. By exceeding a critical amount of Manganese, reactivity in the Zinc bath was deteriorated. This amount was found to be between 2.9 and 3.8 wt% for Si content of 1.5 wt%.